High performance thin layer chromatography fingerprint and antioxidant activities of Cyclea barbata in Thailand - Thummajitsakul, Sirikul; Sitthithaworn, Worrapan; Silprasit, Kun (Agriculture and Natural Resources, 2019)
Cyclea barbata is a commonly used herbal and traditional plant, and its leaves contain a high level of pectin. However, different habitats, jelly extract and leaf age may affect the biocompounds in the leaves. Therefore, a high performance thin layer chromatography (HPTLC) technique was used for preliminary screening of some active leaf compounds from various habitats along with total phenolic analysis and antioxidant activity of this plant from different sources and leaf ages (young, middle and old). The HPTLC results of methanol leaf extract revealed various chemical patterns that were indicated by retention factors (Rf values) in the range 0.15–0.73; unique bands of two samples (P1 and P3) from Phetchabun province were detected under ultra-violet light (Rf = 0.65 at 254 nm and Rf = 0.40 at 366 nm, respectively). Additionally, alkaloid bands were not found in leaf extracts by spraying with Dragendroff’s reagent. A chemical band with antioxidant activity was only found at Rf = 0.50 in old and young fresh leaves following spraying with 2,2-diphenyl-1-picrylhydrazyl. The total phenolic contents of old, fresh leaves had the highest value (525.08 mg gallic acid/g extract), whereas the 2,2’-azino-bis 3-ethylbenzothiazoline-6-sulfonic acid diammonium salt radical scavenging activity of old, dry leaves was highest (97.7%). These results indicated that different Rf values of various phytochemicals and various habitats of C. barbata could be primarily determined using HPTLC analysis. Antioxidant activities were determined using chemical bands and leaf extracts at various ages.